Exploring the Impact of Personality Traits and Death Anxiety Among Healthcare Professionals - Rule, Prince Niel; Lagumbay, Raquelyn; Ramos, Andrea; Cayda, Kendra Jean (Journal of Interdisciplinary Perspectives, 2025)
This study examined the relationship between personality traits and death anxiety among healthcare professionals in a healthcare facility in Davao City using a quantitative-correlational research design. A sample of 40 healthcare professionals was selected through purposive sampling. Two validated questionnaires, the Big Five Inventory and the Death Anxiety Scale, were employed. The findings revealed moderate personality traits among the participants, with agreeableness having the highest mean and neuroticism having the lowest. Death anxiety was also moderately observed. Notably, agreeableness and neuroticism showed significant relationships with death anxiety: agreeableness served as a protective factor, while neuroticism was a risk factor. Despite these findings, the study concluded that there is no significant overall relationship between the combined levels of personality traits and death anxiety among healthcare professionals. These results highlight the complexity of death anxiety and the need for targeted interventions focusing on specific personality traits. The findings suggest that addressing personality traits such as neuroticism and fostering traits like agreeableness could be beneficial in managing death anxiety among healthcare professionals. This detailed understanding underscores the importance of personalized approaches in mental health interventions within healthcare settings. The results suggest the need for healthcare facilities to implement programs to manage stress and foster supportive work environments for professionals to manage death anxiety.